Studi Biologi Sel : Pengamatan Sel Epitel Mukosa Mulut pada Remaja Perokok Aktif - Meysa Al-Fahmi; Antonio Ferdynando Lobo; Sisca Listyanty; Hanif Irsyad; Mutia Jelita Bilorwier; Liss Dyah Dewi Arini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Tobacco use in the form of cigarettes is a risk factor for oral lesions. Exposure to tobacco in cigarettes results in an imbalance between antioxidant enzymes in metabolizing and detoxifying carcinogens in tobacco, which can cause changes in the oral epithelium that will develop into lesions and dysplasia. The purpose of this study was to determine the condition of oral mucosal epithelial cells in adolescent active smokers. This study used a laboratory experimental method. The population in this study were adolescent active smokers. This study used a purposive sampling technique. The sample used was 1 respondent. The variable used in this study was the condition of oral mucosal epithelial cells in adolescent smokers. The method used was the exfoliation cytology method with the technique. The results of the examination of the condition of oral mucosal epithelial cells showed that 100% of respondents showed normal results. The conclusion of this study is the results of the examination of the condition of oral mucosal epithelial cells in adolescent active smokers with normal epithelial cell conditions.